Development of complete silica thin films based on functional hyperbranched polyalkoxysiloxanes. (20th December 2017) - Agrawal, Garima; Zhu, Xiaomin; Moeller, Martin; Choudhary, Veena
Abstract: A precursor polymer has been designed on the basis of an idea of conversion of hyperbranched polymer to an inorganic substance by lithographic procedure. For this purpose hyperbranched polyethoxysiloxane (PEOS) was synthesized via a one-pot catalytic condensation reaction of tetraethoxysilane with acetic anhydride. PEOS was modified with cyclohexanol via a catalytic trans-esterification reaction. The products were characterized by means of 1 H and 29 Si NMR spectroscopy, elemental analysis and size exclusion chromatography. The thin silica films were formed by spin-coating of chloroform solutions of PEOS and cyclohexanol-modified PEOS (CH-PEOS) on silicon wafer substrates with subsequent H2 -plasma treatment. CH-PEOS layer containing a photoacid could be cross-linked upon UV-irradiation. This approach was used to develop patterned thin silica films, which were analyzed by field emission scanning electron microcopy and atomic force microscopy. Well defined sharp silica patterns were obtained and further conversion of the layer to pure silica was carried out by removing organic species using H2 plasma treatment. Graphical abstract: Highlights: Hyperbranched silica precursor polymer for developing complete inorganic films. Silica precursor shows higher storage stability. Films are formed using photoacid and crosslinking upon UV-irradiation. Films are converted to pure silica using H2 plasma treatment.